Incorporation of kenaf core fibers into low density polyethylene/thermoplastic sago starch blends exposed to natural weathering - Sarifuddin, Norshahida; Ismail, Hanafi; Ahmad, Zuraida (Taylor & Francis Group, LLC, 2014)
The landﬁll disposal of a high volume of plastics that take a long time to decompose has led to a tremendous environmental problem. Incorporation of natural polymers and ﬁbers into synthetic polymers accelerates the degradation rate by exposure to atmospheric agents such as sunlight, temperature and rainfall. In this work, thermoplastic sago starch (TPSS) and kenaf core ﬁbers (KCF) from agricultural feed stocks were blended with low density polyethylene (LDPE) for natural weathering studies. The melt-mixed and compressed composite sheets had ﬁber loadings ranging from 0 to 40 wt.%, and were exposed to natural weathering conditions for a period of 3 and 6 months. The deterioration in mechanical, thermal, morphological and weight properties were investigated.